Presence of cagPAI genes and characterization of vacA s, i and m regions in Helicobacter pylori isolated from Alaskans and their association with clinical pathologies. Issue 2 (3rd February 2020) - Miernyk, Karen M.; Bruden, Dana; Rudolph, Karen M.; Hurlburt, Debby A.; Sacco, Frank; McMahon, Brian J.; Bruce, Michael G.
Abstract : Introduction. Gastric cancer is a health disparity in the Alaska Native people. The incidence of Helicobacter pylori infection, a risk factor for non-cardia gastric adenocarcinoma, is also high. Gastric cancer is partially associated with the virulence of the infecting strain. Aim. To genotype the vacA s, m and i and cag pathogenicity island ( cagPAI ) genes in H. pylori from Alaskans and investigate associations with gastropathy. Methodology. We enrolled patients with gastritis, peptic ulcer disease (PUD) and intestinal metaplasia (IM) in 1998–2005 and patients with gastric cancer in 2011–2013. Gastric biopsies were collected and cultured and PCR was performed to detect the presence of the right and left ends of the cagPAI, the cagA, cagE, cagT and virD4 genes and to genotype the vacA s, m and i regions. Results. We recruited 263 people; 22 (8 %) had no/mild gastritis, 121 (46 %) had moderate gastritis, 40 (15%) had severe gastritis, 38 (14 %) had PUD, 30 (11 %) had IM and 12 (5 %) had gastric cancer. H. pylori isolates from 150 (57%) people had an intact cagPAI ; those were associated with a more severe gastropathy ( P ≤0.02 for all comparisons). H. pylori isolates from 77 % of people had either the vacA s1/i1/m1 (40 %; 94/234) or s2/i2/m2 (37 %; 86/234) genotype. vacA s1/i1/m1 was associated with a more severe gastropathy ( P ≤0.03 for all comparisons). Conclusions. In this population with high rates of gastric cancer, we found that just over half of the H. pylori contained an intact cagPAI and 40 % had the vacA s1/i1/m1 genotype. Infection with these strains was associated with a more severe gastropathy.